The effect of physical changes in a furnished indoor environment on Wireless Local Area Network (WLAN) signals - Cheng, Ee Meng; Abbas, Zulkifly; Abd Malek, Mohd Fareq; Khor, Shing Fhan; You, Kok Yeow; Lee, Kim Yee; Abdul Majid, Mohd Shukry; Rojan, Mohd Afendi (IJENS Publisher, 2014)
This paper describes the investigation of the effect on the Wireless Local Area Network (WLAN) signals due to fixed and non-fixed variables in the indoor environment. The measurement system consisted of a spectrum analyzer and a log-periodic antenna. Line-of-sight (LOS) propagation and non-line-of-sight (NLOS) propagation (in furnished rooms) were discussed. All the measurement sites mentioned in this paper are located in the Division of Information Technology at Universiti Putra Malaysia. The furnished rooms included a teaching laboratory, a computer laboratory, and an operating office plus a server room. The effects of the various types of materials at the measurement sites also are described here.